Using Coffee Beans And Peels To Improve Biochemical Changes In Rats With Hyperglycemia (The Review of Diabetic Studies, 2025)
Arabic coffee has several unique characteristics, including its distinctive taste and aroma resulting from the addition of spices such as cardamom and saffron, as well as its health benefits, such as boosting energy and concentration, and strengthening the immune system thanks to its antioxidant properties. Aim: present research aims to enhance the using coffee beans and peels to improve biochemical changes in rats with hyperglycemia.Materials and Methods: Thirty-six male Sprague Dawley mice have been categorized into a normal group (n =6)and a diabetic group (n =30). The 2nd group received an intraperitoneal injection of streptozotocin at a dosage of seventy-five milligrams per kilogram, and individuals exhibiting blood glucose levels over 250 milligrams per deciliter were categorized as diabetic. Rats have been categorized into six groups: (1) non-diabetic group (n =6) received distilled water (2 mL/ day); (2) diabetic control group (n =6) received distilled water (two milliliters per day); (3) diabetic group (n =6) received a basal diet supplemented with 5 % coffee peels; (4) diabetic group (n =6)received a standard diet supplemented with 10% coffee peels; (5) diabetic group (number = six) received a standard diet supplemented with 5% coffee beans; (6) diabetic group (n =6)received a standard diet supplemented with 10% coffee beans. Following twenty-eight days, blood has been drawn, and serum has been extracted to assess glucose, HbA1c, & blood lipids. Results: From the outcomes of biochemical analysis of serum examined plants not only reduced serum glucose, but additionally cured or ameliorated completely the side effects of diabetes mellitus, being liver, kidney, & lipid profile disorders. In present work, coffee (peel and bean) revealed the maximum hypoglycemic effect, reducing serum glucose, besides a considerable reduction of diabetes side effects. Coffee peel is advised to be added to herb formulations assigned for diabetics, since it enhances the therapeutic effect of the herbs.